Alat Pendeteksi Data Vaksinasi Sensor FPM10A dan NODEMCU ESP8266 Menggunakan Metode Sequential Searching - Afrido Soales Sitohang; Andrianningsih (KITA Institute, 2022)
Making a finger vaccination data detection system using the IOT-based FPM10A sensor and Nodemcu esp8266 in order to facilitate the community process during a pandemic. Sequential Search Algorithm is a linear search algorithm, this algorithm performs searches faster because the search process is already in an ordered state. In this pandemic period, in every activity or traveling to a place, now you often have to show proof of vaccination and the community's capacity to use the internet is still not evenly distributed to show vaccination certification, of course this will make it easier, this can also avoid fake vaccination certifications. In this study, in addition to using a fingerprint recognition device, the Nodemcu esp8266 microcontroller and fpm10a sensor are also used as transmission media to the application, making it easier for the public and users of this tool to save costs and time.